Penataan Kondisi Sosial Ekonomi Masyarakat di Lingkungan Rt.002/Rw.002 Keluranan Harapan Mulya - Reni Novia; Muhamad Fachri Hidayat; Muhammad Iqbal Al-Ghifari (Yayasan Literasi Sains Indonesia, 2025)
The Community Service Program (KKN) is a form of higher education implementation aimed at improving the socio-economic quality of the community through empowerment programs. This KKN activity, conducted by students from Institut Bisnis Muhammadiyah Bekasi in RT.002/RW.002, Harapan Mulya Urban Village, focuses on three main issues: (1) MSME development, (2) enhancing children's skills and financial literacy, and (3) educating the community on religious-based corpse care. The program applied participatory, educational, and collaborative approaches involving local stakeholders. The methods used included counseling, training, community service activities, and direct mentoring. The outcomes showed improved public understanding of MSME digitalization through QRIS creation and GoFood accounts, increased children's interest in saving and engaging in productive activities, and enhanced knowledge of corpse management procedures. The involvement of youth organizations and Posyandu also strengthened the sustainability of the program. Evaluation was carried out through field observations and interviews with community leaders. With these positive outcomes, the program is expected to serve as a sustainable model for community service and be replicated in other similar regions.